Using Cellphone in Problem-Based Biology Learning to Improve Students’ Creative Thinking Skills - Elmanazifa, Sintia; Lufri, Lufri (FKIP Universitas Lampung, 2022)
Students' creative thinking skills need to be developed in the learning process. However, the learning process in schools has not fully implemented learning models that develop students' skills. From the results of observations at SMAN 7 Padang, learning at school still does not make use of Information and Communication Technology (ICT) and lacks interest in learning in class. To overcome these problems, the Problem Based Learning (PBL) model which is intervened with the use of ICT is applied. The use of ICT used is utilizing cellphone and internet networks in obtaining broader information. This study aims to analyze the effect of the implementation of the problem-based learning model that is intervened by information technology on students' creative thinking skills. This type of research is quasi-experimental research with a randomized control-group posttest only design. The results of testing the hypothesis, namely tcount > ttable, indicate that the research hypothesis is accepted. Keywords: problem-based learning, information and communication technology, creative thinking skills, cellphone. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1717-1723